Formulation and characterization of tadalafil-loaded orodispersible films with enhanced dissolution rate and membrane permeability - Zhao, Zong Liang; Peng, Dingxin; Liu, Xin; Li, Xue Cheng; Lan, Li Jing; Wu, Xin Hong; Liu, Xue Ai; Cui, Jing Hao; Lee, Beom Jin; Shi, Li Li; Cao, Qing Ri (Journal of Drug Delivery Science and Technology, 2023)
The low solubility of tadalafil (TDF) normally retards the dissolution rate and permeability of the drug in oral mucosa and gastrointestinal tract. The aim of this study was to optimize and evaluate novel orodispersible films (ODFs) loaded with TDF or micronized TDF (MTDF) to enhance the solubility and permeability of the drug. The TDF(or MTDF)-loaded ODFs with polyvinyl alcohol 1788 as a film-forming material, sodium alginate as a disintegrant, polyethylene glycol 400 as a plasticizer, and polysorbate 80 (Tween 80) or sodium lauryl sulfate (SLS) as a surfactant was prepared by using a solvent casting method. In addition, the formulation composition of TDF-loaded ODFs was also optimized in terms of appearance, thickness, disintegration time, mechanical properties, and dissolution rate of films. The SLS-incorporatedODFs showed more reliable dissolution profiles than Tween 80-incorporated ODFs in pH 7.4 PBS (0.5% SLS and 1% Tween 80) as compared to commercial tablet (Cialis®). The dissolution rates of optimal TDF-loaded ODFs (F11) at pH1.2 and pH7.4 were 68.74% and 74.81% at 15 min, 83.04% and 84.95% at 30min, respectively. Compared with Cialis® and F11, MTDF-loaded ODFs (F12) showed faster dissolution rate at 10 min in pH 7.4 PBS (0.5% SLS). There was no significant difference in the in vitro permeability between F11 and F12 in the media containing Tween 80. However, the permeability of F12 was higher than that of F11 if Tween 80 was absent in the dissolution media. In conclusion, novel TDF or MTDF-loaded ODFs were successfully formulated and the ODFs incorporated with MTDF showed higher drug dissolution and membrane permeability, indicating that the ODFs formulated with MTDF may be an alternative to commercial tablets for the treatment of male erectile dysfunction.
Keywords: Dissolution rate; Membrane permeability; Micronization; Orodispersible film; Tadalafil